Research on end-to-end network link delay inference based on link reconstruction-destruction - Yong-sheng LIANG; Bo GAO; Yue ZOU; Ji-hong ZHANG; Nai-tong ZHANG (Tongxin xuebao)
Based on two assumptions,inference model and end-to-end delay data acquisition,an approach to end-to-end network internal link delay inference based on link reconstruction-deconstruction (LRD) was proposed.Pseudo likelihood estimation (PLE) was adopted and the inference problem was divided into independent sub-problems.Inference units with definite solution are determined by LRD.By means of controlling average sampling precision and decreasing inference unit links,the computation complexity of link delay inference was significantly lowered.Experimental study was performed based on model computation and NS2 simulation platform.Theoretical analysis and experimental results show that the approach is accurate and effective.